Impact Of Arabic Online Learning In The Perspective Of How The Brain Learns - Hilmi, Danial (Ijaz Arabi Journal of Arabic Learning, 2021)
The study aims to describe the impact of learning Arabic online and the viewpoint of brain-based learning on these implications. The research used a mixed-method that combines quantitative and qualitative approaches to get a real picture of the implementation of online learning from a neurolinguistic perspective, the data is obtained through the results of questionnaires and studied in a neurolinguistic perspective based on the literature on the theme. The data collection technique was carried out by distributing questionnaires to PKPBA students who carried out Arabic learning through online and literature review on neurolinguistic studies. The results of this study are that the Arabic learning process carried out online has good benefits with varied but not optimal patterns of interaction through blended learning. In contrast, according to neurolinguistics, it is stated that at least any model can maintain how the potential of the brain through language habituation must be consistent with the balance of the left and right brain.